Revisiting the forgotten pandemics: Using multimodality in crafting images of HIV/AIDS in Kenyan newspapers - Kodak, Benard; Anudo, Cellyne; Ogembo, Jack (Research Journal in Advanced Humanities, 2021)
The advent of COVID-19 towards the end of the year 2019 led to radical paradigm shifts in public health management strategies across the world. This at a time when the HIV and AIDS pandemic has been in existence for close to half a century and continues to ravage poor populations of the Third World and developing nations. The World Health organization declared COVID-19 a global pandemic in March 2020. Since then, COVID-19 has been considered a social phenomenon because of the complex nature of the virus’ infection, efforts to develop treatment and the public’s responses to the disease and how it has affected human interactions. Countries around the world responded to this novel pandemic by instituting measures aimed at curbing the spread of the virus. The Kenya Ministry of Health for example, gave several directives aimed at curbing the spread of COVID-19 such as setting up hand washing stations in all public places including homes, banning public gatherings, and wearing protective face masks among others. All attention was thus focused on the novel pandemic, and HIV and AIDS which has been in existence for over four decades seems to have been forgotten. It is against this background that this paper revisits the public health management efforts on HIV and AIDS prior to the advent of the COVID-19 virus as seen in one newspaper advertisement in Kenya about HIV and AIDS.